Orientação para familiares de alunos com paralisia cerebral usuários de sistemas de comunicação suplementar e alternativa - Goldoni, Natalie Iani [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The argumentative and alternative communication area literature discusses the need of filling in the family in the evaluation, implementation and monitoring processes of supplementary and alternative communication. Including user’s family on the decisions along the adapting process, as well as training them as interlocutors should be part of the group of actions adopted by the professional team. However, materials, programs and orientation are still poor for those families. Taking from that, the objective of this paper was systematizing the needed content to orient the families of student’s with cerebral palsy using supplementary and alternative communication. The research was done in two papers: Identify programs of family orientation in the context of supplementary and alternative communication by revision bibliography (Study 1); Identify potentials and problems of children’s families using chart system (Study 2). On the first study fifteen national and international published articles composed the analyzed material. There were identified 118 pieces noting family orientation, clear recommendation or qualitative and relevant information to family advice in supplementary and alternative communication. With this total, only seven parts could be categorized as family orientation, 48 presented recommendation characteristics and 63 were understood as an aspect of alternative communication. Among the given recommendation, a tendency of the authors in considering mediation and professional performance were observed. Parents of students with cerebral palsy using supplementary and alternative communication took part on the second study. They were assisted on a specialized Centre and attended on a workshop of alternative communication program of Alternative Communication and Technology Laboratory on a public University from 2008 to 2012. The collected data were shooting of the capacitation program done on the Laboratory. The analyzing...

A literatura da área da comunicação alternativa discute a necessidade de inserir a família no processo de avaliação, implementação e acompanhamento de sistemas de comunicação suplementar e alternativa. Incluir os familiares do usuário de comunicação suplementar e alternativa nas tomadas de decisão ao longo de todo o processo de adaptação, bem como capacitá-los adequadamente como interlocutores, devem compor o conjunto de ações adotado pela equipe de profissionais. No entanto, são escassos, ainda, os materiais, programas e orientações sistematizadas para serem utilizados com estas famílias. A partir disso, o objetivo do presente estudo foi sistematizar conteúdo necessário para orientação a famílias de alunos com paralisia cerebral usuários de sistemas suplementares e alternativos e comunicação. Desta forma, a pesquisa foi realizada em dois estudos: Identificar por meio da Revisão bibliográfica os programas de orientação familiar no contexto da comunicação suplementar e alternativa (Estudo 1); Identificar as potencialidades e problemas de famílias das crianças e jovens usuários de sistemas gráficos (Estudo 2). No estudo 1 compuseram o material de análise quinze artigos publicados em um periódico nacional e dois internacionais. Foram identificados 118 excertos que remetiam à orientação familiar, recomendação clara ou forneciam indicadores qualitativos relevantes para o aconselhamento familiar em Comunicação suplementar e alternativa. Deste total, apenas sete trechos puderam ser categorizados como sendo de orientação familiar, 48 tinham características de recomendação e 63 foram compreendidos como sendo indicativos de recomendação a respeito de algum aspecto da comunicação alternativa. Dentre as recomendações identificadas, foi observada a tendência dos autores em tecer considerações a respeito de aspectos da mediação e da atuação profissional na área. No estudo 2 participaram da...
Keywords: Educação especial; Família; Paralisia cerebral; Comunicação; Special education